S66 A randomised crossover trial of pressure support ventilation (PSV) versus pressure controlled ventilation (PCV) in stable hypercapnic Chronic Obstructive Pulmonary Disease (COPD). (16th November 2010) - Brignall, K A; Murphy, P B; Moxham, J; Polkey, M; Davidson, A C; Hart, N
Abstract : Introduction: PSV, rather than PCV, is often the preferred mode of ventilatory support in stable hypercapnic COPD patients, although this is supported by limited data. We hypothesised that PCV would be equivalent to PSV with similar patient-ventilator synchrony, nocturnal ventilation, gas exchange and sleep quality with similar adherence to non-invasive ventilation and improvements in health related quality of life (HRQL). Method: HypercapnicCOPD patients (daytime PaCO2 >6 kPa) were enrolled and randomised to PSV (low back up rate) or PCV for 6 weeks. Patients had baseline anthropometric, HRQL and gas exchange measurements, were re-assessed at 6 weeks and crossed over to the other arm with the final assessment at 12 weeks. Sleep quality was assessed using a sleep diary and nocturnal actigraphy (Actiwatch AW4, CamNTech, Cambridge, UK) for 2 weeks prior to each assessment. Subjective patient-ventilator synchrony was assessed with a questionnaire (Score 0–3, 0=good synchrony). At 6 and 12 weeks, all measurements were repeated, including ventilator adherence. Results: 12 patients were enrolled. However, three were unable to tolerate NIV and 1 failed to adhere to the study protocol. Four commenced on PSV and 4 commenced on PCV. Mean (±SD) age 72±8 years, BMI 32±9 kg/m 2, FEV1 /FVC 54±14%, FEV1 29±11%, PaCO2 8.6±1.7 KPa and PaO2 7.3±1.4 KPa. Mean IPAP 28±4 cm H2 O and mean EPAP 5±3 cm H2 O. Backup rate for PSV was 6 bpm and PCV was 16±1 bpm. The mean nocturnal respiratory rate was 14±3 bpm and 16±1 bpm with triggering compliance of 90±9% and 24±10% for PSV and PCV, respectively. According to the patient-ventilator synchrony questionnaire, patients reported an increased awareness of ineffective efforts (0.7±0.5 vs 0.1±0.3; p=0.03) and a short inspiratory time (0.7±0.7 vs 0.1±0.3; p=0.03) during PSV, but there was no difference in self-reported sleep comfort and quality. Furthermore, there were no between group differences in change in PaCO2, ventilator use or nocturnal actigraphy. Although there were similar between group improvements in HRQL, the respiratory symptom domain of the Severe Respiratory Insufficiency Questionnaire favoured PSV (p=0.02). Conclusion: Despite clinicians' perception that PSV has an advantage over PCV for the management of patients with stable hypercapnic COPD, these pilot data do not necessarily support this view.